2011
DOI: 10.1016/j.paid.2011.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Brief assessment of schizotypy: Developing short forms of the Wisconsin Schizotypy Scales

Abstract: Abstract:The Wisconsin Schizotypy Scales-the Perceptual Aberration, Magical Ideation, Physical Anhedonia, and Revised Social Anhedonia Scales-have been used extensively since their development in the 1970s and 1980s. Based on psychometric analyses using item response theory, the present work presents 15-item short forms of each scale. In addition to being briefer, the short forms omit items with high differential item functioning. Based on data from a sample of young adults (n = 1144), the short forms have str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 31 publications
2
109
0
Order By: Relevance
“…As in Study 1 described earlier, we administered the 15-item short form of the Physical Anhedonia Scale (Winterstein et al, 2011). Experience-sampling procedure.…”
Section: Methodsmentioning
confidence: 99%
“…As in Study 1 described earlier, we administered the 15-item short form of the Physical Anhedonia Scale (Winterstein et al, 2011). Experience-sampling procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, it occurs on a continuum of hedonic tone, or perceived intensity of pleasantness (Gabbay et al, 2012; Germine, Garrido, Bruce, & Hooker, 2011; Ritsner et al, 2011). The use of scales can determine the degree of hedonic tone or severity of anhedonia (Chapman, Grimshaw, & Nicholls, 2011; Kirkpatrick et al, 2011; Miettunen et al, 2011; Winterstein et al, 2011). Even people with severe symptoms of anhedonia can attain pleasure from a few sources (Meehl, 1990), and “normal” individuals also have varying degrees of hedonic tone (Grillo, 2012).…”
Section: Concept Analysis Resultsmentioning
confidence: 99%
“…Indeed, several researchers have indicated that CogDis is related to unpleasant evaluation of unusual experiences (Schofield and Claridge, ), or cognitive attenuations and poor emotional processing (Kerns and Becker, ; Cappe et al ., ). A problem is certainly the lack of consideration of disorganised symptoms in studies that found attenuated cognitive functioning relating to positive symptoms (Lenzenweger and Korfine, ; Laws et al ., ) and that most of the psychometric tools used in these studies do not distinguish between the two symptom dimensions (Eysenck and Eysenck, ; Chapman et al ., ; Chapman et al ., ; Eckblad and Chapman, ; Peters et al ., ; Winterstein et al ., ).…”
Section: Discussionmentioning
confidence: 97%